Preparation of face cream for uvanapidaka viz -a -viz acne with special reference to Manjishtadi oil - Dasunika, R.T.; Herapathdeniya, S.K.M.K.; Nallaperuma, D.M. (Faculty of Graduate Studies, University of Kelaniya, 2024)
In Ayurveda, Uvanapidaka is a specific type of skin disease which has a direct effect on skin beauty. Ayurveda Susruta samhitha mentioned that vitiation of Kapha, Vata and Rakta together results in Uvanapidaka, which has an appearance of a prickles of Bombax malabaricum tree. Malahara kalpana is the most effective external pharmaceutical preparation for uvanapidaka according to Ayurveda and it can be correlated with ointments, creams, and lotions in modern pharmaceutics. The objective of this study was to prepare a cream for uvanapidaka by using Manjishtadi oil according to the references of Ayurveda pharmacopeia. Manjishtadi oil has a nourishing effect on skin, improves skin complexion, reduce skin inflammations. Decoction of Rubia cordifolia, Glycyrrhiza glabra, resin of Croton laccifer, Citrus medica, goat milk and water (16 parts) were mixed with 4 parts of sesame oil and 1 part of kalka to prepare the oil. Kalka was made by grinding dry powders R. cordifolia, G. glabra and C. medica with resin of C. laccifer. Manjishtadi Oil and bee’s wax was mixed the ratio of 1:6 to convert it into a cream (sample A). Sample B was prepared by using preservative and sample C was prepared by adding fragrance. Physico-chemical analysis and phytochemical analysis including HPTLC were performed for the cream. The results revealed that total ash content (1.24%) and pH value (5) were within the normal range also suitable for the skin. Methanol extract was positive for tannins, alkaloids, and flavonoids. Chemical profile of the product was obtained using HPTLC fingerprint (Toluene:Hexane:Ethylacetate 1:1:1 v/v% ). There was no any significant change in color, odor or appearance of all three samples during 40 days of shelf-life determination. Physico-chemical analysis concludes that the cream is having standard quality and purity. Phytochemical analysis determines that the cream may have antioxidant, anti-fungal and anti-bacterial properties, which are beneficial for skin diseases
Keywords: anti-oxidant; manjishtadi oil; ointment; skin complexion; uvanapidaka